2008
DOI: 10.1073/pnas.0805828106
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the conformational states of F 1 -ATPase as determined from its crystal structure and single-molecule rotation

Abstract: F1-ATPase is a rotary molecular motor driven by ATP hydrolysis that rotates the ␥-subunit against the ␣3␤3 ring. The crystal structures of F1, which provide the structural basis for the catalysis mechanism, have shown essentially 1 stable conformational state. In contrast, single-molecule studies have revealed that F1 has 2 stable conformational states: ATP-binding dwell state and catalytic dwell state. Although structural and single-molecule studies are crucial for the understanding of the molecular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
83
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 38 publications
7
83
0
Order By: Relevance
“…S5). Because a wide range of rotations of the foot of the central stalk is observed in the crystal structures, even when the enzyme is believed to be in the same catalytic state, it is very difficult to relate the crystallographic results to the discrete states observed in the "single molecule" biophysical experiments (21,22).…”
Section: Resultsmentioning
confidence: 99%
“…S5). Because a wide range of rotations of the foot of the central stalk is observed in the crystal structures, even when the enzyme is believed to be in the same catalytic state, it is very difficult to relate the crystallographic results to the discrete states observed in the "single molecule" biophysical experiments (21,22).…”
Section: Resultsmentioning
confidence: 99%
“…1A. In the known structures of F 1 -ATPase, which apparently are near the "catalytic dwell" state, the state in which catalysis occurs (6,7), the β E subunit conformation is partly to fully open and is very different from those of the β TP and β DP subunits, which are closed and very similar to each other (SI Appendix, SI1).…”
mentioning
confidence: 99%
“…However, we still do not have a clear structure function correlation that involves both the chemistry and the conformational coupling. The challenge became even more exciting in view of the remarkable progress in single-molecule studies that directly visualized the γ-subunit rotation in a unidirectional way, while revealing several plausible intermediates that have not been observed in any of the crystal structures (9)(10)(11).…”
mentioning
confidence: 99%
“…For example, despite the fact that the structures of several ATPases have been elucidated (e.g., refs. 4 and 8) and recent advances in detailed elucidation of some key steps have been made (9)(10)(11), it is not completely clear at what stage in the reaction energy is actually released and, in turn, what is the nature of the energy conversion process. Some workers have suggested that the major source of the energy release is the conversion of the free energy of ATP binding into elastic strain, which is subsequently released by a coordinated and tightly coupled conformational mechanism (6).…”
mentioning
confidence: 99%